Net zero energy buildings : case studies and lessons learned - Reeder, Linda (Architect) (New York : Routledge, 2016)
Net Zero Energy Buildings provides a broad look at the current state of the net zero energy building movement. Linda Reeder highlights all the seminal early-21st-century net zero projects, from new large office buildings, historic retrofits, to K-12 schools across a range of climate zones in the US. Not only does Reeder provide 18 case studies to show cost effective and mainstream net zero projects in operations, but she also provides unique insights into common best practices critical for any owner or designer looking to go net zero in their next project.--COVER.
-- Pt. 1. Office buildings -- Bullitt Center : Seattle, Washington -- DPR Construction Phoenix Regional Office : Phoenix, Arizona -- National Renewable Energy Laboratory Research Support Facility : Golden, Colorado -- The David and Lucile Packard Foundation Headquarters : Los Altos, California -- Wayne N. Aspinall Federal Building and U.S. Courthouse : Grand Junction, Colorado -- Pt. 2. Educational and community buildings -- Berkeley Public Library West Branch : Berkeley, California -- Bosarge Family Education Center : Boothbay, Maine -- Center for Sustainable Landscapes : Pittsburgh, Pennsylvania -- Hood River Middle School Music and Science Building : Hood River, Oregon -- Lady Bird Johnson Middle School : Irving, Texas -- Locust Trace AgriScience Center Academic Building : Lexington, Kentucky -- Painters Hall Community Center : Salem, Oregon -- Pt. 3. Retail -- TD Bank - Cypress Creek Branch : Fort Lauderdale, Florida -- Walgreens in Evanston : Evanston, Illinois -- Pt. 4. Production homes and multi-family housing -- Camp Lejeune Midway Park Duplex : Jacksonville, North Carolina -- Eco-Village : River Falls, Wisconsin -- zHome Townhomes : Issaquah, Washington -- Paisano Green Community : El Paso, Texas -- Pt. 5. Lessons learned -- Shared lessons for future net zero energy projects.
Includes bibliographical references and index.
Keywords: Sustainable buildings